2007
DOI: 10.1063/1.2435319
|View full text |Cite
|
Sign up to set email alerts
|

Large-mode-number magnetohydrodynamic instability driven by sheared flows in a tokamak plasma with reversed central shear

Abstract: The effect of a narrow sub-Alfvénic shear flow layer near the minimum qmin of the tokamak safety factor profile in a configuration with reversed central shear is analyzed. Sufficiently strong velocity shear gives rise to a broad spectrum of fast growing Kelvin-Helmholtz (KH)-like ideal magnetohydrodynamic modes with dominant mode numbers m,n∼10. Nonlinear simulations with finite resistivity show magnetic reconnection near ripples caused by KH-like vortices, the formation of turbulent structures, and a flatteni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…Due to mutual interaction between the two resonant surfaces, the DTM is a much stronger instability than the single tearing mode. The dynamic properties of the DTM for different magnetohydrodynamical (MHD) models have been widely studied under various conditions, such as external shear flow, [9][10][11] bootstrap current, 12 anomalous electron viscosity, 13 and collisionless effects. [14][15][16] Recently, it is suggested that the internal transport barrier may be related to the strong shear flows associated with the DTM.…”
mentioning
confidence: 99%
“…Due to mutual interaction between the two resonant surfaces, the DTM is a much stronger instability than the single tearing mode. The dynamic properties of the DTM for different magnetohydrodynamical (MHD) models have been widely studied under various conditions, such as external shear flow, [9][10][11] bootstrap current, 12 anomalous electron viscosity, 13 and collisionless effects. [14][15][16] Recently, it is suggested that the internal transport barrier may be related to the strong shear flows associated with the DTM.…”
mentioning
confidence: 99%
“…In the linear phase and in the slab geometry, plasma flow shear is found to either increase or decrease the linear growth rate, depending on the plasma viscosity, the magnetic shear and the strength of flow shear. 8,9 When the velocity shear is strong enough, it will give rise to short wave-length Kelvin-Helmholtz (KH) instabilities [10][11][12] and excitation of Alfvé n resonances. [13][14][15] In the nonlinear phase, the flow shear is found to decrease the saturated island width 16 and leads to deformation of magnetic island.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for choosing these three rotation profiles is that they have different shear amplitudes and signs at rational surfaces . This is a very important research area in terms of rotational stabilization of MHD instabilities in fusion plasmas (Chu 1998; Bierwage, Yu & Günter 2007; Chapman et al. 2011, 2012; Wahlberg, Graves & Chapman 2013).…”
Section: The Equilibrium Profiles and The Rotation Profilesmentioning
confidence: 99%
“…At present, two mainstream methods are envisaged for the RWM stabilization. One is the active control technique utilizing magnetic coil systems (Fransson et al 2000;Bondeson et al 2001;Liu et al 2004Liu et al , 2005aLiu et al ,b, 2009Liu et al , 2010Drake et al 2005;Gregoratto et al 2005;Martin et al 2009). The other can be called the passive control method, largely relying on additional energy damping often associated with the toroidal flow of the plasma.…”
Section: Introductionmentioning
confidence: 99%